(untitled) (International Journal of Food and Nutritional Sciences, 2020)
India is a culturally diverse nation with a wide range of climates, from tropical regions in the south to alpine climes in the north. India’s cuisine is influenced by environmental factors such as climate, agricultural practices, and climate variation.